Frequency Modulation for Preschoolers with Hearing Loss - Mulla, Imran; McCracken, Wendy (Seminars in Hearing, 2014)
The aim of this research was to evaluate and explore the benefits of frequency-modulated (FM) technology with preschool children with hearing aids. The research was of a longitudinal prospective design, including both quantitative and qualitative analysis. This article will focus on the quantitative results only. Daily diaries, data-logging, and questionnaires were used to collect quantitative data. Five of the seven families were able to establish regular FM use in a range of environments and settings with the most frequent being at home, in the car, at the nursery, during shopping, and when outdoors. Situational analysis of FM use was established and compared over time using the FM Listening Evaluation for Children questionnaire. Improvements in listening in noise, auditory only, and distance were identified over time. The Language Developmental Snapshot was used to monitor language development over the duration of the study. Results indicated that children who were at risk at the start of the study were within normal levels or close by the end of the study. The current study provides a unique contribution to the existing literature and together with future research can be integral to the provision of FM/remote microphone technology as standard for preschool children with hearing aids.
Keywords: Hearing loss; pediatrics; hearing aids; wireless; FM; remote microphones